2022
DOI: 10.1097/md.0000000000029472
|View full text |Cite
|
Sign up to set email alerts
|

Is there a correlation between preoperative neutrophil-to-lymphocyte, platelet-to-lymphocyte, and lymphocyte-to-monocyte ratios and postoperative pain in video-assisted thoracoscopic surgery?

Abstract: Many thoracic surgery procedures are now performed with video-assisted thoracoscopic surgery (VATS). Postoperative pain is a common condition in patients undergoing VATS. In this study, we aimed to investigate whether neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) are effective in evaluating postoperative pain in patients undergoing VATS.This prospective observational study was performed between March 2021 and September 2021 at a tertiary thorac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A high N/L ratio in the preoperative period has been noted to be associated with high postoperative pain scores and analgesic consumption. [24][25][26] The preoperative Neutrophil, Lymphocyte, and N/L ratios of the patients included in our study were similar among the groups. Therefore, it can be stated that these markers did not affect the postoperative pain status as the groups were similar in terms of inflammatory parameters in the preoperative period.…”
Section: Discussionmentioning
confidence: 92%
“…A high N/L ratio in the preoperative period has been noted to be associated with high postoperative pain scores and analgesic consumption. [24][25][26] The preoperative Neutrophil, Lymphocyte, and N/L ratios of the patients included in our study were similar among the groups. Therefore, it can be stated that these markers did not affect the postoperative pain status as the groups were similar in terms of inflammatory parameters in the preoperative period.…”
Section: Discussionmentioning
confidence: 92%
“…Pain after VATS is a common condition and adequate control of postoperative pain in patients undergoing VATS is very important for the prevention of pulmonary complications (17). Adequate management of postoperative pain provides early mobilization, lowers hospital stay, lowers costs, and increases patient satisfaction (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…For the early mobilization of patients after surgery, coughing should be ensured so that lung secretions can be cleared. This can only be possible by providing adequate analgesia to the patient (17,22). However, with using more opioids than necessary while providing postoperative pain control, side effects, such as respiratory depression and…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the previous reports, preoperative inflammatory biomarkers had been independent predictors of prognostic markers who undergo thoracic surgery, potentially linked to smoking. [38][39][40] In addition, there were found that preoperative inflammatory parameters were associated with postoperative pain in many operations, [41][42][43][44][45] but the relationship between them was still controversial. In this study, we found the relevance between neutrophils and CPSP in elderly patients.…”
mentioning
confidence: 99%